What and How Much Do Children Lose in Academic Settings Owing to Parental Separation? - Corrás, Tania; Seijo, Dolores; Fariña, Francisca; Novo, Mercedes; Arce, Ramón; Cabanach, Ramón G. (Frontiers in Psychology, 2017)
The literature has firmly established an association between parental separation and school failure. Nevertheless, parental separation does not affect academic aptitudes. Thus mediators explain such relationship. A field study was designed to identify and quantify damage in the mediating variables between parental separation and school failure (i.e., external school adjustment, aversion to institution, aversion to learning, aversion to instruction, aversion to teachers, indiscipline). A total 196 children, classified into 3 age cohorts: 109 in Level 1 (from 8 to 11 years), 46 in Level 2 (from 12 to 14 years), and 41 in Level 3 (15 or more years), were assessed in school adjustment and in underlying dimensions of school (mal)adjustment. The results showed significant effects of parental separation in school adjustment and in the underlying dimensions to maladjustment in the three classification levels. The magnitude of damage increased with age i.e., small in level 1, moderate in 2, and large in 3. Damage in all the sub-dimensions underlying school (mal)adjustment was quantified. The implications of the results for the design and implementation of prevention and intervention programs for children from separated parents are discussed.